Sources of resilience in the Filipino wife's responses to spousal infidelity. . [article]. - Gonzales, Teodulo P. .
The purpose of this study was to identify patterns of resilience in the Filipino wife's responses to spousal infidelity, by examining associations between demographic characteristics spiritual and religious practices and two dependent variables. resilience as measured by the Sense of Coherence Scale(Antonovsky, 1998,1987). and the Dyadic Adjustment Scale(Spanier 1976). The sample consisted of 304 Filipino wives from Metro Manila, Laguna and Bulacan,; all of whom experienced a husband's infidelity. The results showed that wife's depression and worry about finances were negatively correlated with Sense of Coherence. Wife's problem solving skills and religious support variables were positively correlated with the Sense of Coherence. Married/living together(infidelity stopped) is negatively correlated with Dyadic Adjustment. Husband's attending the Mass is positively correlated with the Dyadic Adjustment.